Dampak Difusi Arus dalam Konduktor untuk Nilai Beban Resistif Lebih Besar dari Impedansi Saluran - A.M Shiddiq Yunus; Apollo Apollo (Politeknik Negeri Ujung Pandang, 2013)
Research on current diffusion into the conductor is one of important segments in electrical engineering field of study. The main purpose of the study is to recognize the behaviors and characteristics of current diffusion in conductor for further development in the future. The results of the research would be very useful, particularly in the transmission line study. In this paper, study will be focused at the characteristic of current diffusion in conductor due to its variation impedance value of load particularly when resistive load is larger than the conductor impedance (Zo).